Sustaining Local Values in Character Education: Strategies for Effective Implementation in Community Learning Center Contexts - Eli Farlina; Sri Nurhayati; Agus Hasbi Noor (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
This study explores the integration and sustainability of local values in character education within the context of Community Learning Centers (CLCs) in Indonesia, focusing on PKBM Melati Batujajar. Employing a case study approach within a qualitative research framework, data were collected through semi-structured interviews, participant observations, and document analysis. The findings reveal the critical role of local values such as